2019
DOI: 10.4025/actasciagron.v41i1.39874
|View full text |Cite
|
Sign up to set email alerts
|

Can an increase in nitrogen rate mitigate damages caused by uneven spatial distribution of maize plants at the sowing row?

Abstract: An uneven distribution of maize plants at the sowing row can decrease grain yield. This work was carried out to evaluate the effect of an increasing nitrogen rate on maize agronomic performance under different variation coefficients of plant spatial distributions at the sowing row. The experiment was conducted in Lages, Santa Catarina State, South Brazil. Three variation coefficients (VC) of plant spatial distribution (0, 50, and 100%) were tested. At the 0 level, seeds were evenly distributed 17 cm from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The use of spacing that is too wide is also very inefficient, because the yield per unit area of land obtained decreases with a decrease in the number of plant populations. This is in accordance with the opinion of [11] stated that if the increase in population is still below the increase in competition, the increase in production or yield of crops will be achieved higher at denser spacings. Based on the results of research that has been carried out on farm business analysis on spacing and doses of chicken manure, it is stated that the R:C ratio obtained is more than one, which means that farming in the cultivation of gambas can be said to be profitable or feasible to do (Figure 1).…”
Section: Resultssupporting
confidence: 90%
“…The use of spacing that is too wide is also very inefficient, because the yield per unit area of land obtained decreases with a decrease in the number of plant populations. This is in accordance with the opinion of [11] stated that if the increase in population is still below the increase in competition, the increase in production or yield of crops will be achieved higher at denser spacings. Based on the results of research that has been carried out on farm business analysis on spacing and doses of chicken manure, it is stated that the R:C ratio obtained is more than one, which means that farming in the cultivation of gambas can be said to be profitable or feasible to do (Figure 1).…”
Section: Resultssupporting
confidence: 90%
“…In the 2018/2019 growing season, the Brazilian average productivity of first corn crop was only 8.2 Mg ha -1 (Conab, 2020). However, experiments carried out by Kolling et al (2019) and Panison et al (2019) showed that first corn crop has a yield potential higher than 15 Mg ha -1 in this region. The generation of information that allows better understanding of management practices for high corn grain yield is fundamental to enhance the cereal-cultivated first crop area, enabling rotation with soybean in spring/summer and increasing the sustainability and resilience of grain production systems in southern Brazil.…”
Section: Introductionmentioning
confidence: 82%
“…The relative chlorophyll content associated with NDVI is an indication of conversion of light energy into chemical energy, i.e. into photoassimilates (Kolling et al, 2019). Thus, Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, cultivation ranges from small properties to large commercial plantations; according to Conab (2020), national production of 100.48 million tons is estimated for the 2019/2020 harvest, with average productivity of 5.5 t ha -1 ; obtained through the set of management techniques to achieve high productive ceilings. One technique is the use of modern hybrids coupled with modifications in plant arrangement, intensification of nitrogen fertilization, and the use of products aimed at maximizing productivity (Kolling et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation